In Vitro Antiinflammatory Activity of Bajakah (Spatholobus littoralis) Stem Extract - Diah Wulandari Rousdy; Elvi Rusmiyanto Wardoyo (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2023)
The plant of Bajakah tampala (Spatholobus littoralis Hassk) has been utilized in traditional medication. Previous studies have proven the existence of in vivo anti-inflammatory activities of Bajakah plant (S. littoralis) in lowering the degree of carrageenan-induced paw oedema in mice. This study aims to determine the anti-inflammatory mechanism of S. littoralis extract in vitro through an approach of enzyme inhibition involved in the inflammatory reaction. The concentration of ethanol extract of Bajakah used was 0.1; 0.2; 0.4; 0.8; 1.6 mg/ml. The parameters measured were lipoxygenase enzyme inhibition, protein denaturation inhibition, protease enzyme inhibition, as well as plasma membrane stabilization. The results of the study showed the potential of the ethanol extract of Bajakah stems in inhibiting the inflammatory process viewed from the ability to inhibit inflammation-related enzymes. S. littoralis extract concentration of 1.6 mg/ml showed the best inhibition of the protein denaturation process (75.9%), the inhibition of trypsin protease enzyme (26.1%) and the stability of erythrocyte membrane (93.7%). However, the extracts of S. littoralis did not provide inhibition for the lipoxygenase enzyme in the range of 0.2-3.8%. This study proves the role of S. littoralis extract in the anti-inflammatory mechanism. It has the potential to be developed into standardized herbs.